Convection Anisotropies of Cosmic Rays in Highly Magnetized Plasma - Yiran Zhang; Siming Liu (The Astrophysical Journal)
Recently, Y. Zhang & S. Liu proposed a turbulent convection model for multiscale anisotropies of cosmic rays (CRs), with an assumption of isotropic diffusion such that the anisotropies are statistically isotropic. However, this assumption may be unrealistic for TeV CRs, whose observations have revealed the significance of the local interstellar background magnetic field. To meet the difficulty, the turbulent convection scenario needs to be extended to cover anisotropic diffusion. In this paper, we focus on the parallel diffusion with isotropic pitch-angle scattering, which may be an approximation to the transport process driven by weak hydromagnetic waves in a magnetic flux tube, where fluctuations of the wave velocities lead to the turbulent convection. The consequence is the breaking of the statistical isotropy, while the overall shape of the angular power spectrum, $\overline{C_{\ell }}\propto {\ell }^{-γ -1}$ ( ℓ ≫ 1), remains similar to that in the isotropic diffusion model, where ℓ is degrees of spherical harmonics and γ is the turbulence spectral index of the convection field. It is then expected that the power-law index of the TeV CR small-scale angular power spectrum can be explained with the Kolmogorov law γ = 5/3, irrespective of the background magnetic field to some extent.